New strategies for doping control - Lippi, G.; Banfi, G.; Franchini, M.; Guidi, G. C. (Journal of Sports Sciences, 2008)
Doping in sports is commonplace. The prevention of harm to the athlete, the guarantee of fair play, and a level playing field for all competitors are the basis of the current anti-doping strategies. As healthcare systems are forced to allocate increasing resources to prevent and treat the prevailing pathologies worldwide, funding for anti-doping campaigns will necessarily be restricted. Ideally, additional resources should be devoted to increasing the number of athletes tested, the panels of tests used, and the frequency of out-of-competition controls. Since doping prevention cannot be considered a priority for most healthcare systems, such an approach is unaffordable and an alternative framework should be devised, focused primarily on harm reduction rather than fair play. The identification of abnormal deviations from reference values, regardless of pathological or artificial causes, would allow the athlete to be followed and tested using conventional laboratory tests, which are affordable to governments and healthcare systems and available to clinical laboratories. Although this strategy would not detect cheating, it would safeguard athletes' health.